PERAN GENDER SEBAGAI VARIABEL MODERASI DALAM PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT - Zailani, Rinawati; Gunartati, Gunartati; Fanani, Johan (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2022)
Service quality is the producer's behavior to meet consumers' needs and achieve satisfaction. This study was conducted to determine the effect of reliability, assurance, responsiveness, attention, and tangibles of service quality on pleasure, and to examine the moderation effect in this relationship. Gender is expected to strengthen the influence of the five dimensions of service quality on satisfaction. The research method used is a survey method with a quantitative research approach. The sample in this study amounted to 100 people, taken using a non-probability sampling technique because the actual number of the research population is not known with certainty. The data analysis technique used multiple regression and moderated regression analysis (MRA). The results showed that of the five dimensions of service quality, only the dimensions of responsiveness, attention, and tangibles significantly affected satisfaction. Gender can fully moderate the influence of the assurance dimension of service quality on happiness, whereas gender strengthens the influence of the assurance dimension of service quality on satisfaction. These results become a reference for agencies to further improve the quality of services by paying attention to gender.